PENGARUH PENGGUNAAN HANDPHONE TERHADAP INTERAKSI SOSIAL TEMAN SEBAYA SISWA SMA 2 SUNGAI RAYA - Sumiati, Sumiati; Rustiyarso, Rustiyarso; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe use of mobile phones in schools, besides having an effect on learning outcomes, mobile phones tend to have an influence on peer interactions at school. As a result of carrying the cellphone students are busier and more concerned with their cellphones than interacting with fellow friends around them. Students play more mobile phones like chatting with friends in their cellphone contacts. then the main problem in this study is "How the Effect of Mobile Use on Social Friends Peer Interactions of SMA 2 Sungai Raya Students". The form of the method used and considered appropriate in this study is the form of Interrelationship Studies with the intention of knowing the relationship and the influence of the use of mobile phones on peer social interactions in SMA 2 Sungai Raya. From the results obtained, 61.42% shows the use of mobile phones in SMA 2 Sungai Raya students. In addition, 67.85% of the ability to do activities with peers and amounted to 64.76% can be seen from the calculated data of 0.465 and calculation of the table of 1.989, indicating that there is a positive and significant influence between the use of mobile phones to social interactions of student peers SMA Negeri 2 Sungai Raya.Â Â Keywords: Handphone, Peers, Social Interaction